2007
DOI: 10.1002/ejoc.200601062
|View full text |Cite
|
Sign up to set email alerts
|

Gold Catalysis: Selectivity Problems in Hydroarylations with Pyrroles

Abstract: Gold‐catalyzed reactions of pyrrole derivatives with methyl vinyl ketone preferentially give rise to doubly substituted products, with an excess of methyl vinyl ketone even triple substitutions can be observed. This is independent of the electronic nature of substituents on the pyrrole ring, even substrates with electron‐withdrawing acyl substituents in 1‐, 2‐ or 3‐position show this behavior. The NH group of the pyrrole ring may be unprotected, no competing hydroamination is observed. In an intramolecular com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 29 publications
(12 reference statements)
1
22
0
Order By: Relevance
“…It should be noted that intermolecular hydroarylation with substituted pyrroles was less investigated, possibly due to the difficulty of controlling the regioselectivity. 12,20 To clarify the reaction mechanism, we tried the following control experiments (Scheme 6). It was found that the desired product 2a was not observed upon stirring 1a and acetophenone under the standard reaction conditions, implying that the reaction did not proceed via hydration of alkyne followed by condensation with α-amino ketone.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…It should be noted that intermolecular hydroarylation with substituted pyrroles was less investigated, possibly due to the difficulty of controlling the regioselectivity. 12,20 To clarify the reaction mechanism, we tried the following control experiments (Scheme 6). It was found that the desired product 2a was not observed upon stirring 1a and acetophenone under the standard reaction conditions, implying that the reaction did not proceed via hydration of alkyne followed by condensation with α-amino ketone.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…We also expect that, using this protocol, substrates such as bromoindoles could lead to the formation of bromocarbazoles, which could subsequently be cross-coupled. 14 A tentative mechanism to explain the formation of carbazole 2 is given in Scheme 5. 15 The carbophilic gold catalyst activates alkyne 1 to form a -complex intermediate 1I.…”
Section: Scheme 1 Synthetic Plan For Carbazolementioning
confidence: 99%
“…It should be noted that chemoselectivity is a well-known problem in gold-catalysed reactions with pyrroles, because the mono-alkylated product is more nucleophilic than the startingp yrrole, and this can result in multiple alkylations. [35] Remarkably,t his chemoselectivity issue was not observed under our conditions. To our surprise, however,n or egioselectivity was observed between reactiona tt he a and b positiono ft he pyrrole (3cl/3cl'',1 :1, entry 12).…”
Section: Resultsmentioning
confidence: 56%
“…Although N ‐methylpyrrole 2 l was reported to be unreactive under Gagné’s original conditions, the reaction proceeded under our optimised protocol with a reasonable yield (58 %), good allene regioselectivity (>20:1), and excellent chemoselectivity (entry 12). It should be noted that chemoselectivity is a well‐known problem in gold‐catalysed reactions with pyrroles, because the mono‐alkylated product is more nucleophilic than the starting pyrrole, and this can result in multiple alkylations . Remarkably, this chemoselectivity issue was not observed under our conditions.…”
Section: Resultsmentioning
confidence: 99%